2016
DOI: 10.1007/s00299-016-2020-0
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic expression and functional characterization of type III polyketide synthase mutants from Emblica officinalis Gaertn

Abstract: Functional characterization and ectopic expression studies of chalcone synthase mutants implicate the role of phenylalanine in tailoring the substrate specificity of type III polyketide synthase. Chalcone synthase (CHS) is a plant-specific type III polyketide synthase that catalyzes the synthesis of flavonoids. Native CHS enzyme does not possess any functional activity on N-methylanthraniloyl-CoA, which is the substrate for acridione/quinolone alkaloid biosynthesis. Here, we report the functional transformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…It has been observed that CHS shows wide substrate specificity range as it could accept both aliphatic and aromatic CoA esters to produce various reaction products including the unnatural aromatic polyketide [55]. The differential enzyme activity of different CHS isoforms with different substrates has also been reported in Humulus lupulus [56], Gerbera hybrida [57], Emblica officinalis [58] and others. The differential enzyme activity of Ga CHS2 towards different substrates indicates its evolutionary expansion possibly due to gene duplication “Fig 6”.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that CHS shows wide substrate specificity range as it could accept both aliphatic and aromatic CoA esters to produce various reaction products including the unnatural aromatic polyketide [55]. The differential enzyme activity of different CHS isoforms with different substrates has also been reported in Humulus lupulus [56], Gerbera hybrida [57], Emblica officinalis [58] and others. The differential enzyme activity of Ga CHS2 towards different substrates indicates its evolutionary expansion possibly due to gene duplication “Fig 6”.…”
Section: Discussionmentioning
confidence: 99%
“…Later, the role of flavonoids in the plant–microbe interaction arsenal was proposed by [ 88 ]. Studies have been conducted on Aegle marmelos [ 89 ] and Emblica officinalis [ 90 ] to unveil the role of active site amino acid residues and the phenotypic changes in their mutants. The overexpression of the quinolone synthase gene in Aegle marmelos induced improved growth, chlorophyll content, and photosynthetic efficiency.…”
Section: Targeting Secondary Metabolite Biosynthetic Pathways For Multiple-stress Resilience and Induced Autoimmunitymentioning
confidence: 99%